Phosphohistone H3 as the standard of immunohistochemical study in the assessment of differentiation level of oropharyngeal zone squamous cell carcinomas - А. V. Lysak; О. О. Dyadyk (Patologìâ)
Verification and grading of tumors of oropharyngeal areas, determination of their malignancy potential remain an urgent problem as well as diagnosis and prognosis today.